UNIMAS TESL undergraduates' preference of classroom activities in teaching the literature component during teaching practice - Wong,, Siew Fang. (UNIMAS, 2009)
This study aimed to examine UNIMAS TESL undergraduates’ preference of classroom activities in teaching the literature component during Teaching Practice. The research objectives are to find out the classroom activities employed by UNIMAS TESL undergraduates to teach the literature component, their reasons for employing such activities, their perception of the usefulness of classroom activities employed, and lastly the most preferred classroom activity to teach the literature component as well as their reasons for preferring such an activity. 70 TESL undergraduates who were in their third and fourth year respectively and have taught literature component during Teaching Practice were chosen as the respondents for the study. Survey research design with questionnaire as the main instrument was used in this study. The findings showed that respondents have employed a wide range of classroom activities to teach the literature component. Group or class discussion, jumbled sentences,summary writing, role play, and prediction exercises were the most frequently employed classroom activities to teach the literature component. Reasons given by the respondents for employing such activities indicated that students’ needs were the greatest concern. Group or class discussion has the highest ratingand this activity was reported as the most preferred classroom activity and the reasons identified were scaffolding each others’ learning, building students’ confidence, the nature of the activity itself which was time-saving, enhancing critical and creative thinking skills, and encouraging interaction as well as interest of the students